2021
DOI: 10.1186/s12977-021-00550-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from HTLV-1 infected cells modulate target cells and viral spread

Abstract: Background The Human T-cell Lymphotropic Virus Type-1 (HTLV-1) is a blood-borne pathogen and etiological agent of Adult T-cell Leukemia/Lymphoma (ATLL) and HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP). HTLV-1 has currently infected up to 10 million globally with highly endemic areas in Japan, Africa, the Caribbean and South America. We have previously shown that Extracellular Vesicles (EVs) enhance HTLV-1 transmission by promoting cell–cell contact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 114 publications
(112 reference statements)
2
36
0
Order By: Relevance
“…Lastly, we observed that the HTLV-1infected cells contained higher intracellular env RNA compared to secreted env RNA (EV-bound) at each timepoint (Figure 5A,B). This is consistent with observations that HTLV-1 primarily exists intracellularly, and that infectious virion release occurs sporadically in infected cells [14,18,56,58]. Collectively, these data indicate that HTLV-1 RNA synthesis is increased post-release/induction and that viral RNA can be found in the extracellular environment.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Lastly, we observed that the HTLV-1infected cells contained higher intracellular env RNA compared to secreted env RNA (EV-bound) at each timepoint (Figure 5A,B). This is consistent with observations that HTLV-1 primarily exists intracellularly, and that infectious virion release occurs sporadically in infected cells [14,18,56,58]. Collectively, these data indicate that HTLV-1 RNA synthesis is increased post-release/induction and that viral RNA can be found in the extracellular environment.…”
Section: Discussionsupporting
confidence: 90%
“…The infectivity of the 24-h samples but not of the 6-h samples could be augmented by the presence of EVs. This is in line with data from Figure 1 (lane 10) that demonstrate that the concentration of EVs peaks at 24 h. Collectively, these results imply that virions released at 24 h are indeed infectious, and the presence of EVs may contribute to their infectivity, since EVs from virally infected cells have been found to contain viral proteins and RNA that can increase the pool of surrounding cells susceptible to infection [14,[18][19][20]32,51,52].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations